Práticas de reconhecimento da pessoa surda como inovação social: o caso do IFSC campus Palhoça bilíngue - Pacheco, Marcos (2020)
The research here presented has the purpose of analyzing how the recognition practices developed in the IFSC Campus Palhoça Bilíngue configure themselves as social innovation. In order to make such an investigation viable, we decided to prepare a case study based on an IFSC unit elected as an observatory for this condition, thus dialoguing with specialists, protagonists in the process of implementing the pedagogical and institutional proposal of this singular IFSC academic unit, made up of deaf people, be students, TAES or teachers. The guiding question of the research intended to lead the knowledge of this reality from two central and complementary concepts, capable of translating the rich and relevant experiences narrated by the research subjects, namely: the practices of recognition and social innovation, within the scope of guarantee of the right to education of deaf people, aiming to contribute with the efforts of organizational studies, composing a valuable research territory in the scope of social innovation and propagating the deafness in the perspective of the struggle for recognition, verifying quite complex effects, in which people through resistence strategies and freedom practices manage to define more satisfactory ways of recognition and existence.